Burnout in Health Professionals According to Their Self-Esteem, Social Support and Empathy Profile - Molero Jurado, María del Mar; Pérez-Fuentes, María del Carmen; Gázquez Linares, José Jesús; Barragán Martín, Ana Belén (Frontiers in Psychology, 2018)
Introduction: Professionals in the healthcare field are in situations that could be a source of stress and sometimes develop burnout syndrome. Self-esteem, social support, and empathy are variables which intervene and influence the appearance of this syndrome. Objective: Identify healthcare professional profiles based on self-esteem, empathy and perceived social support, and analyze the extent to which these profiles show differences in developing burnout. Method: The sample was made up of 719 healthcare professionals with a mean of 38.52 years of age. The Short Questionnaire of Burnout, the Rosenberg Self-Esteem Scale, the Perceived Social Support Questionnaire and the Basic Empathy Scale were used. Results: The results of a cluster analysis with self-esteem, empathy, and perceived social support showed four groups/profiles. Two of them, which included professionals with low self-esteem, differed in the rest of the characteristics. Furthermore, significant differences in burnout scores were found among the groups identified. Conclusion: The results show the need to study burnout with attention to individual and or social characteristics, where self-esteem is shown to be one of the explanatory variables making the main differences among the groups.